2016
DOI: 10.1017/s095026881600251x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enhanced biosecurity and selected on-farm factors onCampylobactercolonization of chicken broilers

Abstract: This is the author's accepted manuscript of the following article: GEORGIEV, M., BEAUVAIS, W. and GUITIAN, J. (2016) 'Effect of enhanced biosecurity and selected on-farm factors on Campylobacter colonization of chicken broilers', Epidemiology and Infection, pp. 1-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…A well-designed and planned biosecurity approach at farm level have been established as a fundamental method to counteract colonization of flocks (Georgiev et al, 2017). The present review will focus on the avian management practices on poultry farms and what effect these have on Campylobacter prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…A well-designed and planned biosecurity approach at farm level have been established as a fundamental method to counteract colonization of flocks (Georgiev et al, 2017). The present review will focus on the avian management practices on poultry farms and what effect these have on Campylobacter prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Among units with poorer biosecurity, a physical access barrier and dedicated footwear were protective risk factors. In both the foregoing studies, the association with superior biosecurity was lower, or absent, following thinning (Georgiev et al., ; Smith et al., ).…”
Section: Field Investigations Into Biosecurity and Hygienementioning
confidence: 99%
“…An independent multivariable analysis on U.K. data collected at the same time also concluded that thinning was a risk factor separate from flock age (Lawes et al., ). Other quantitative analytical studies have implicated thinning in counteracting the reduced colonization associated with enhanced biosecurity, among the birds remaining at final depopulation (Georgiev et al., ; Smith et al., ). By contrast, a retrospective multivariable modelling analysis of data from The Netherlands concluded that thinning was not significantly associated with flock colonization by Campylobacter once flock age and season had been accounted for (Russa et al., ).…”
Section: Field Investigations Into Biosecurity and Hygienementioning
confidence: 99%
See 2 more Smart Citations